Migratory earthquake precursors are dominant on an ice stream fault - Barcheck, G. (Sci Adv, 2021)
Simple fault models predict earthquake nucleation near the eventual hypocenter (self-nucleation). However, some earthquakes have migratory foreshocks and possibly slow slip that travel large distances toward the eventual mainshock hypocenter (migratory nucleation). Scarce observations of migratory nucleation may result from real differences between faults or merely observational limitations. We use Global Positioning System and passive seismic records of the easily observed daily ice stream earthquake cycle of the Whillans Ice Plain, West Antarctica, to quantify the prevalence of migratory versus self-nucleation in a large-scale, natural stick-slip system. We find abundant and predominantly migratory precursory slip, whereas self-nucleation is nearly absent. This demonstration that migratory nucleation exists on a natural fault implies that more-observable migratory precursors may also occur before some earthquakes.